तीरे-तीरे नर्मदा - Vegad, Amritlal (Madhya Pradesh Hindi Granth Academy, 2010)
The book is a travelogue to the river Narmada which is considered to be one of the sacred rivers of India.
Teere Teere Narmada
Keywords: तीरे-तीरे नर्मदा; Teere Teere Narmada; Travelogue; Hindi; Hindi